Screening for palliative care needs: pilot data from German Comprehensive Cancer Centers - Roch, Carmen; Heckel, Maria; Oorschot, Birgitt van; Alt-Epping, Bernd; Tewes, Mitra (JCO oncology practice, 2021)
PURPOSE: - - Guidelines recommend several screening tools to identify patients with complex palliative needs. This diversity and lack of structural recommendations offer a wide scope for implementing screening. Against this background, the current status of implementation at German Comprehensive Cancer Centers (CCCs) funded by the German Cancer Aid has not yet been investigated. - - METHODS: - - e-mail survey of the 17 hospital sites of the 13 CCCs. The questionnaire asked for structural characteristics of the centers as well as preconditions of the screening process. Structurally established screening procedures (one item) and standardized workflows, modes of performance, screening tools (four items), modes of training how to screen, and responsibilities (two items) were assessed. - - RESULTS: - - In a 2-month period, 15 hospital sites responded; seven hospital sites conducted a palliative care needs (PCN) screening. Only one hospital site carried out PCN screening in almost all oncology departments, but only with the distress thermometer. Other hospital sites determined palliative needs by assessing physical symptoms using the Integrated Palliative Care Outcome Scale or the Minimal Documentation System, and two hospital sites combined tools to determine both physical and psychological stress. The type of screening varied from paper-pencil-based to tablet computer-based documentation. The main barriers to implementation were identified as a lack of human resources and a lack of structural conditions. - - CONCLUSION: - - There is a lack of consensus among palliative care specialists and oncologists in the CCCs supported by the German Cancer Aid in PCN screening as well as of structured guidelines and the professional association. Structural requirements should be adapted to these needs, which include both technical and human resources. A combined psycho-oncologic and palliative care screening might help to formulate best practice recommendations.